Potencial de generación de energía eléctrica a partir de la biomasa residual del proceso de extracción de palma de aceite en la zona norte de Colombia (2021)
The energy potential of the residual oil palm biomass generated in seven extraction plants located in northern Colombia is evaluated through a cogeneration system with extraction turbine – condensation. For all the cases analyzed, the available biomass not only covers the energy requirements of the process, but it can also supply a surplus of energy. The energy potential of residual biomass ranges from 22.5 - 46.5 MW per year for the cases studied. For palm oil mills with capacities between 21 – 41 tRFF-1 it is estimated that it is possible to obtain surplus electricity between 1.7 – 8.9 MW, considering that the energy use of the empty fruit bunch as fuel can increase between 40 – 60 % the energy provided by the kernel shell and fiber. Regarding environmental performance, the calculated GHG emissions were 1 – 3 g CO2eq per kWh for the cases studied. By replacing the electricity of the national interconnected system, the energy generated by biomass could mitigate between 214 - 385 g CO2eq per ton of fresh fruit bunch per year. Depending on the availability of the empty fruit bunch, its energy use can increase the replacement of emissions by 60 – 80%. Electricity generation can be developed at a level cost of electricity between 131 – 223 COP kWh-1 for the palm oil mills studied considering a ten-year investment, which could be economically attractive considering that the cost of selling electricity in Colombia stood between 113 - 321 COP kWh-1 for 2019.